Frequency reconfigurable E‐shaped patch antenna for medical applications. Issue 9 (27th June 2016) - Kumar, Jayendra; Talukdar, F. A.; Basu, Banani
ABSTRACT: Article proposes reconfigurable E‐shaped patch antenna using PIN diode to switch the antenna between two frequency states: 335–565 MHz, 1.29–1.42 GHz and 2.03–2.28 GHz in multiband and 300–645 MHz in single band. Placement of the rectangular slots operates the patch in multiband. Single band is achieved using a bandpass filter. Parasitic element improves the impedance characteristics. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2214–2217, 2016